2015
DOI: 10.1016/j.fertnstert.2014.12.096
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation of oocytes is not associated with altered deoxyribonucleic acid methylation patterns in children from in vitro fertilization or intracytoplasmic sperm injection

Abstract: IVM-induced epigenetic changes in offspring, if any, are relatively small in magnitude and/or infrequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Consistent with earlier studies,27, 28, 29, 30, 31 individual alleles with > 50% aberrantly methylated CpGs were considered as epimutations. Table 1 presents the average EMRs of 8 TS genes (10 amplicons) in 79 BC patients (EO and HR) and 80 unaffected controls.…”
Section: Resultsmentioning
confidence: 79%
“…Consistent with earlier studies,27, 28, 29, 30, 31 individual alleles with > 50% aberrantly methylated CpGs were considered as epimutations. Table 1 presents the average EMRs of 8 TS genes (10 amplicons) in 79 BC patients (EO and HR) and 80 unaffected controls.…”
Section: Resultsmentioning
confidence: 79%
“…However, patients with oligoasthenoteratozoospermia with a partial hypomethylation of H19 presented a reduced fertilization rate following intracytoplasmic sperm injection (ICSI). A previous analysis of the methylation status of ICSI infants with a low birth weight revealed hypermethylation at the MEST gene in one of the infants included in the study (119,120).…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 87%
“…In terms of epigenetics, a study has reported that IVM exerts no significant effect on the methylation level of maternal imprinted genes, such as LIT1, SNRPN, PEG3, and GTL2, in human oocytes [42]. After an imprinted gene examination was carried out for infant chorionic cells and cord blood obtained from IVM and a standard stimulation protocol, no significant difference was observed between the two methods [43,44]. Currently, the follow-up of IVM-aided pregnancies shows that the IVM technique does not increase the risk of pregnancy, the rate of maternal complications, and the rate of neonatal abnormalities [45,46].…”
Section: Clinical Application and Safety Of Ivmmentioning
confidence: 99%